Pneumopericardium Secondary to Esophago‐Pericardial Fistula. Issue 8 (27th July 2013) - Caselli, Stefano; Serdoz, Andrea; Palumbo, Barbara; Todi, Fiammetta; Palma, Mario Di; Serdoz, Roberto
Mini‐Abstract We report the clinical case of a 63‐year‐old woman with a squamous cell carcinoma in the distal esophagus complicated by an esophago‐pericardial fistula and pneumopericardium. This is a rarely observed condition usually associated with a high mortality because may result in cardiac tamponade. However, as the esophago‐pericardial fistula was open and the air was free to enter and exit throughout the cardiac and respiratory cycle without significantly increasing pericardial pressure, our patient showed only a mild hemodynamic impairment without overt clinical signs of cardiac tamponade.